Tipos de personalidad y Vigorexia en usuarios de gimnasios. Riobamba, 2021 - Martinez Vargas, Erica Lissette (2022)
ABSTRACT: This study was carried out to analyze the type of personality associated with vigorexia in users of the Riobamba 2021 gyms. The methodology was based on a quantitative approach with a non-experimental field design and a descriptive level. The population corresponds to 2300 users of gyms located in Riobamba, leaving the sample represented by 300 participants who were selected through intentional non-probabilistic sampling, who were evaluated through the SEAPsI questionnaire, which allowed determining the type of personality, while the variable vigorexia was measured. The study used the ADONIS complex questionnaire and obtained a higher prevalence of the male sex, represented by 51.3%, with an average of 24 years. There is evidence of a predominance of the paranoid, anancastic, dependent, and histrionic types in terms of personality type regarding body image, 60.3% express concern about their physical appearance, and only 6.7% do so at a pathological level. Finally, there is no relationship between the study variables. It is concluded that the characteristics found in gym users represent risk factors in the development of vigorexia. No correlation was found between the variables. The most frequent personality types correspond to characteristics associated with obsession, perfectionism, egocentrism, and need for approval; these correspond to concern for body image and fixation with specific ideas, such as achieving a certain standard of beauty imposed by society.